Learning Modern Linux - Hausenblas, Michael (O'Reilly Media, Inc., 2022)
Whether you're new to Linux or have some experience, this practical book shows you how to master various tasks with this operating system--not just system administration. Cloud native professionals including developers, architects, DevOps practitioners, and site reliability engineers will learn how to use and program Linux in different modern environments, from embedded systems such as the Raspberry Pi to the virtual machine of your cloud provider of choice. Along the way, you'll gain hands-on experience with modern terminals, shells, and commands, use Linux networking, and learn how to manage your workloads, all with the goal of implementing modern Linux observability. You'll also understand how to run Linux applications in modern ways by using containers, systemd, modern filesystems, and immutable distros such as Flatcar and Bottlerocket. With this book, you will: Use Linux as a modern programming environment, not just as an admin tool Learn critical components such as the kernel, terminal multiplexer, human-friendly shells, and portable scripting Become familiar with access control, from file permissions to capabilities Understand the role of filesystems as a fundamental building block in Linux Gain hands-on experience with the Linux networking stack and tooling Learn how to apply modern operating system observability to manage your workloads Share data using SSH, rsync, and cloud sync mechanisms.